2022
DOI: 10.3389/fmars.2022.895611
|View full text |Cite
|
Sign up to set email alerts
|

Plastic-Associated Microbial Communities in Aquaculture Areas

Abstract: Microorganisms colonize plastics in the aquatic environment but their composition on plastics used in aquaculture remains poorly studied. Microorganisms play a significant role in aquaculture in terms of water quality and the health of cultivated species. In the current study, we explored the composition of microorganisms on floating plastics and their surrounding water collected from ponds and open aquaculture areas. Using scanning electron microscopy, the diversity of microbial communities, primarily diatoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…These included PET, PP, HDPE, and Nylon-6. As fossil fuel-based plastics remain by far the most widespread polymer types in production and in the environment to date, they are also the most prevalent forms of plastic used in aquaculture [ [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. It has been shown that microplastics are present in aquaculture systems, where they likely originate from feed, clothing, and the components of the systems i.e., filtration equipment and tanks [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These included PET, PP, HDPE, and Nylon-6. As fossil fuel-based plastics remain by far the most widespread polymer types in production and in the environment to date, they are also the most prevalent forms of plastic used in aquaculture [ [43] , [44] , [45] , [46] , [47] , [48] , [49] ]. It has been shown that microplastics are present in aquaculture systems, where they likely originate from feed, clothing, and the components of the systems i.e., filtration equipment and tanks [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies on native plastic‐associated biofilms do not experimentally assess plastic degradation abilities of these communities (Basili et al, 2020 ; Kirstein et al, 2019 ; Lobelle & Cunliffe, 2011 ; Mohsen et al, 2022 ; Pinto et al, 2019 ; Wallbank et al, 2022 ; Zettler et al, 2013 ). A few studies have characterized polystyrene‐associated bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…The recent rapid expansion of the shrimp aquaculture industry influenced the ecological balance of the aquaculture pond and resulted in a surge of diseases causing significant economic losses [1][2][3]. Microalgae plays a crucial role in the aquatic environment required for successful shrimp cultivation [4,5]. The technique of microalgae ecology control, namely adding beneficial live microalgae to establish a benevolent microalgae population and enhance the water quality in aquaculture ponds, is a successful technique for addressing the issues [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%